Citizen Engagement to the Anti-Drug Campaign: the Case of Philippines - Queenie Pearl V. Tomaro; Dyah Mutiarin (ARISTO, 2019)
The study identifies mechanisms wherein Filipino students are able to engage in promoting a drug-free community and the efforts of the Philippine National Police to provide avenue for citizen engagement. Employing the Spectrum of Public Participation introduced by the International Association for Public Participation, the study investigates specific actions that the citizens would willingly partake in support of Duterte’s Drug War. From a sample of 194 students, the research was able to gather responses through close-ended self-reported questionnaire survey and from reports of the Philippine National Police. The study revealed that in all levels of the Public Participation Spectrum, the students are willing to be engaged with the Anti-Drug efforts. Also, efforts from the end of the Police were revealed to have not only be secluded in the inform level but has also reached the level of ‘empower’. Hence, the government of the Philippines must capitalize on these avenues to promote a sustainable and community-based Anti-Drug Campaign.